PENGARUH EDUKASI PADA ORANG TUA TENTANG PUDING JAGUNG UNTUK MENCEGAH STUNTING TERHADAP ANAK DI SD KARTIKA II-3 PALEMBANG - Widianti, Sherly; Yonada, Hesti (Jurnal Kesehatan dan Pembangunan, 2025)
Stunting is a growth disorder in children caused by inadequate social stimulation, repeated infections, and malnutrition. The issue of stunting occurring in developing countries like Indonesia will become a health problem for society and must be seriously addressed. One of the actions taken by health services in an effort to prevent stunting in children is health education about corn pudding. The purpose of this research is to determine the impact of educating parents to prevent stunting in children. The Method analysis in this study is a quantitative research with a pre-experimental type of research. The research design used is a pre-post test design, with a one group pretest and post test design. The population in the study consists of parents and children at Kartika II-3 Elementary School in Palembang, with a sample of 74 people selected based on inclusion and exclusion criteria. The instruments used were questionnaires and e-booklets. The data analysis used is Univariate and Bivariate. The results obtained from the measurements before and after the health education pre-test showed an increase from 41.9% to 60.8%. The result of the Wilcoxon Hypothesis Test, as seen from the Sig. (2-tailed) value, is 0.000. Therefore, if the p value < 0.05 (Ho is rejected, Ha is accepted). It can be concluded that there is an influence of education on parents about corn pudding to prevent stunting in children at SD Kartika II-3 Palembang. It is hoped that this education can be continuously implemented by educational institutions and health professionals as a promotive and preventive effort to reduce stunting rates, as well as to develop other nutritious local food menu variations to optimally support children’s growth and development.